Needs, Challenges and Objectives for Biotechnology and Agriculture in Africa - Nyiira, Z. M. (International Service for National Agricultural Research, 2001)
According to World Health Organization's observations, the world population has grown more than five-fold in just under 200 years to reach five billion. Projections suggest an extra three billion in the next 20 years. Today, Africa contributes 13% of the world's population. At the present rate of growth, that number will double in the next 25 years. This imponderable population expansion makes the achievement of economic equity very difficult; it adds problems of food insecurity and environmental sustainability to the broader issues of international trade. This state of affairs threatens our combined ability to provide for secure livelihoods, improved health standards and greater international stability. With regard to food and agricultural needs, increasing food production efficiency seems to be the only long-term, sustainable solution to our food requirements.